Risk factors for candidemia mortality in hospitalized children - Fabio Araujo Motta; Libera Maria Dalla-Costa; Marisol Dominguez Muro; Mariana Nadal Cardoso; Gledson Luiz Picharski; Gregory Jaeger; Marion Burger (Elsevier, 2017)
Objective: To evaluate risk factors associated with death due to bloodstream infection caused by Candida spp. in pediatric patients and evaluate the resistance to the main anti-fungal used in clinical practice. Methods: This is a cross-sectional, observational, analytical study with retrospective collection that included 65 hospitalized pediatric patients with bloodstream infection by Candida spp. A univariate analysis was performed to estimate the association between the characteristics of the candidemia patients and death. Results: The incidence of candidemia was 0.23 cases per 1000 patients/day, with a mortality rate of 32% (n = 21). Clinical outcomes such as sepsis and septic shock (p = 0.001), comorbidities such as acute renal insufficiency (p = 0.01), and risks such as mechanical ventilation (p = 0.02) and dialysis (p = 0.03) are associated with increased mortality in pediatric patients. The resistance and dose-dependent susceptibility rates against fluconazole were 4.2% and 2.1%, respectively. No resistance to amphotericin B and echinocandin was identified. Conclusion: Data from this study suggest that sepsis and septic shock, acute renal insufficiency, and risks like mechanical ventilation and dialysis are associated with increased mortality in pediatric patients. The mortality among patients with candidemia is high, and there is no species difference in mortality rates. Regarding the resistance rates, it is important to emphasize the presence of low resistance in this series. Resumo: Objetivo: Avaliar os fatores de risco associados ao óbito por infecção da corrente sanguínea causada pela Candida spp em pacientes pediátricos e avaliar a resistência ao principal antifúngico usado na prática clínica. Métodos: Este é um estudo transversal, observacional e analítico com coleta retrospectiva que incluiu 65 pacientes pediátricos internados com infecção da corrente sanguínea por Candida spp. Foi realizada uma análise univariada para estimar a associação entre as características dos pacientes com candidemia e o óbito. Resultados: A incidência de candidemia foi de 0,23 casos em cada 1000 pacientes/dia, com taxa de mortalidade de 32% (n = 21). O resultado clínico como sepse e choque séptico (p = 0,001), comorbidades como insuficiência renal aguda (p = 0,01) e riscos como ventilação mecânica (p = 0,02) e diálise (p = 0,03) estão associados ao aumento da mortalidade em pacientes pediátricos. As taxas de resistência e susceptibilidade dose-dependente contra o fluconazol foram de 4,2% e 2,1%, respectivamente. Não foi identificada nenhuma resistência à anfotericina B e equinocandina. Conclusão: Os dados de nosso estudo sugerem que a sepse e choque séptico, insuficiência renal aguda e riscos como ventilação mecânica e diálise estão associados ao aumento da mortalidade em pacientes pediátricos. A mortalidade entre pacientes com candidemia é alta, e não há nenhuma diferença nas taxas de mortalidade entre as espécies. Sobre a resistência, é importante enfatizar a presença de baixa resistência nesta série. Keywords: Candidemia, Pediatric mortality, Bloodstream infection, Blood culture, Palavras-chave: Candidemia, Mortalidade pediátrica, Infecção da corrente sanguínea, Hemocultura